Analysis of Extreme Gastronomy Tourism as a Potential Pandemic in Tomohon City, North Sulawesi, Indonesia - Verena Lunardy; Budi Setiawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Extreme gastronomy tourism can usually be defined in many ways, be it because of the cooking methods or the interesting ingredients. Some countries like China and Thailand have unique gastronomy, and so does the city of Tomohon in Indonesia. In fact, it has turned into one of the world’s threads since the extreme ingredients were part of the pandemic’ causes. Not to mention, most of them are taken from the wildlife where we can not predict whether they have been vaccinated or not yet. This trouble will eventually cause the countries all over the world would start another lockdown which will also affect the tourism due to lack of mobility, on the other hand tourism has turned into one of the factors on why the world’s increased recently. In short, it can be concluded that the impact of pandemic can stop the tourism activity and affecting on a country’s economy too. This journal is reviewing journals literature where were taken from Google Scholar, Nature and Pubmed. Pandemic mostly happened due to the dissemination of virus in many ways which are direct contact or indirect contact. In fact, most of them are caused by food and spread through the physical touch and fluids, in addition the longer the chain of the virus will cause more toxicity to the other host. And the worst the diseases, the later will it resolves and causing an economic instability. It will eventually impact the economy flow and stability.